Environmental Awareness : Bacterial contamination of hand made beverage . (Journal of Faculty of Education, 2021)
Processed street cold beverage for the public round bus terminals in localities  in Khartoum State were examined for the MPN Coliforms and faecal Coliforms / 100ml    There was faecal contamination of 70%for water used for the processing of beverage.88%of orange beverage ,100%of mango and guava beverage & ice is used as constituent of cold beverage.    Results of the questionnaire, showed that the unhygienic environment ,the untrained cold beverage vendors with bad habits and the shortage of public water cycles lead to the contamination of street cold beverages.    Food consumers were found to prefer house cold beverages to street cold beverage, but sometimes they find themselves in need to use street cold beverages especially during the hot weather.     The financial limitations of the public health authorities made them unable to execute their responsibility towards cold beverage  and food handlers as it should be done .
Keywords: Bacterial contamination; Environmental Awareness